Frequency-based current differential protection for VSC-MVDC distribution lines. (May 2020) - Li, Meng; Luo, Yiping; Jia, Ke; Bi, Tianshu; Yang, Qixun
Highlights: The proposed differential protection is immune to line capacitance. Utilizes the Discrete Wavelet Transform to extract the frequency-dominion characteristic of the differential current. Proposes a method that can select a suitable mother wavelet for the Discrete Wavelet Transform impersonally. Proposes a dead zone criterion to assist the protection in handling near-end faults. Abstract: The current of line distributed capacitance might affect the performance of current differential protection, which becomes more serious in DC systems. This paper proposes the frequency-based current differential protection for VSC-MVDC distribution lines to solve the above problem. The protection identifies internal faults using the ratio of low-frequency energy to high-frequency energy of the differential current. Unlike the existing current differential protection, the proposed protection: (1) is not disturbed by the current of the line distributed capacitance that is the brake component instead of the maloperation component to the proposed protection; (2) can tolerate the interference of the noise that is high-frequency. The protection criteria are presented, and the settings are analysed. The dead zone component is proposed to handle near-end faults. The test results have shown that the proposed protection is not affected by the line-distributed capacitance and can correctly operate under 50 Ω fault resistance. It can also tolerate 20 dB of white noise and 40 μs of synchronisation error.